2009
DOI: 10.1073/pnas.0908699106
|View full text |Cite
|
Sign up to set email alerts
|

Long-term natural variability and 20th century climate change

Abstract: Global mean temperature at the Earth's surface responds both to externally imposed forcings, such as those arising from anthropogenic greenhouse gases, as well as to natural modes of variability internal to the climate system. Variability associated with these latter processes, generally referred to as natural long-term climate variability, arises primarily from changes in oceanic circulation. Here we present a technique that objectively identifies the component of inter-decadal global mean surface temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 27 publications
7
73
1
Order By: Relevance
“…Moreover, coupling frequency between the ocean and atmosphere (once a day in MPI-ESM-LR and HadGEM2-ES simulations) might also be insufficient to fully capture climate variability in state-of-theart ESMs. This could support the assertion that the response of models to secular climate change may also be underestimated, since a more naturally variable ocean-climate system will likely be more sensitive to imposed external forcings (von Storch and Zwiers, 1999;Swanson et al, 2009). However, the piControl derived estimates of natural internal variability used in this analysis are shown to be consistent with observed variance using a standard residual consistency test and comparison of simulated noise with two observational estimates (Sect.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, coupling frequency between the ocean and atmosphere (once a day in MPI-ESM-LR and HadGEM2-ES simulations) might also be insufficient to fully capture climate variability in state-of-theart ESMs. This could support the assertion that the response of models to secular climate change may also be underestimated, since a more naturally variable ocean-climate system will likely be more sensitive to imposed external forcings (von Storch and Zwiers, 1999;Swanson et al, 2009). However, the piControl derived estimates of natural internal variability used in this analysis are shown to be consistent with observed variance using a standard residual consistency test and comparison of simulated noise with two observational estimates (Sect.…”
Section: Discussionsupporting
confidence: 57%
“…Removing both interannual and multidecadal SST variability from the observed global mean SAT record results in a climate signal that is monotonic (Swanson et al, 2009;Thompson et al, 2009). Swanson et al (2009) used a suite of climate model simulations to examine resultant global mean temperature variability after removing internal natural climate variability driven by SSTs.…”
Section: Resultsmentioning
confidence: 99%
“…Swanson et al (2009) used a suite of climate model simulations to examine resultant global mean temperature variability after removing internal natural climate variability driven by SSTs. They showed that removing the natural variability of SSTs from global mean temperature resulted in a monotonic warming trend during the 20th century.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations